The biometric potential of transient otoacoustic emissions. (16th April 2009) - Swabey, Matthew A.; Chambers, Paul; Lutman, Mark E.; White, Neil M.; Chad, John; Brown, Andrew; Beeby, Stephen
Whilst the hearing capabilities of the ear are well known and extensively studied, less well known is the fact that the ear can produce sounds. These faint sounds are called otoacoustic emissions and are an involuntary feature of the biomechanical system employed to hear low amplitude sounds. Several distinct types of emission are known; of these, one particular type, transient otoacoustic emissions (TEOAEs), shows potential as a biometric. This paper graphically presents examples of TEOAEs to demonstrate the specificity of TEOAEs to an individual and their stability over a six month period of time. Several large datasets (760 and 561 subjects) and a smaller dataset are numerically analysed to classify individuals and quantify permanence over six months. It was discovered that a high level of classification performance can be obtained using the raw time-pressure data without transformation.